Smithian Growth through Creative Organization - Legros, Patrick; Newman, Andrew F.; Proto, Eugenio (The Review of Economics and Statistics, 2014)
We model technological progress as an external effect of organizational design, focusing on how factories, based on labor division, could spawn the Industrial Revolution. Dividing labor, as Adam Smith argued, facilitates invention by observers of production processes. However, entrepreneurs cannot internalize this benefit and choose labor division to facilitate monitoring. Equilibrium with few entrepreneurs features low wage shares, and high specialization, but a limited market for innovations. Conversely, with many entrepreneurs, there is a large market for innovation but little specialization because of high wage shares. Technological progress therefore occurs with a moderate scarcity of entrepreneurs. Institutional improvements affect growth ambiguously.